A recommender of physical games for learning programming and computational thinking / Mohammad Ahsan Habib - Mohammad Ahsan , Habib (2019)
Keeping students engaged while teaching programming courses is a big challenge for instructors in general, even with the availability of all modern facilities in a classroom. There are numerous approaches to teaching programming such as through online and offline software applications, digital games, Lego bricks, and robotic aids as well as physical activities such as board games, dancing, and unplugged computational thinking (CT) activities. This type of activities is called active learning approach. The objective of the present research is to design, develop, and evaluate a programming and computational thinking assistive tool to bridge the gap through physical and tactile games. The research methodology starts with qualitative preliminary study that was conducted by observing 121 students on different stages and arranged semi-structured interview sessions for 18 randomly selected students. In this study, CT elements are identified and have been mapped to programming codes. Following that, a prototype called Code Analyzer was developed which consists of four main components. i.e. user interface, Control, CT element calculator, and Instructors’ window components. This prototype tool is intended to guide instructors to choose suitable physical or tactile activities by analysing students’ code in relation to CT elements.